PENGARUH MOTIVASI KERJA, IKLIM ORGANISASI DAN EMPLOYEE ENGAGEMENT TERHADAP KINERJA MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA DEPARTEMEN PRODUKSI PT POMI KABUPATEN PROBOLINGGO - Iwan Priyanto (Ar-Ribhu : Jurnal Manajemen dan Keuangan Syariah, 2022)
The achievement of the goals of the organization/institution will be carried out if its human resources show high work performance. To achieve this, organizations/agencies must be able to create conditions that can encourage and enable employees to develop and improve their abilities and skills optimally. Employees who work in an organization / agency should be treated as well as possible, so that employees have good performance and the goals of the organization / agency are achieved. This research includes explanatory research. The sample that will be used by the researcher is the employees of the Production Department of PT POMI Paiton, Probolinggo Regency totaling 58 people. The data collected in this study are primary data obtained through questionnaires. The method used in this research is a questionnaire (questionnaire). The results of this study are (1). Job motivation has no significant effect on job satisfaction. (2). Work motivation has a significant effect on performance. (3). Organizational climate has a significant effect on job satisfaction. (4). Organizational climate has no significant effect on performance.(5). Employee Engagement has a significant effect on Job Satisfaction. (6).Employee Engagement has a significant effect on performance. (7). Job Satisfaction has no significant effect on performance. (8). Work Motivation has a significant effect on Performance through Job Satisfaction. (9). Organizational climate has a significant effect on performance through job satisfaction. (10).Employee Engagement has a significant effect on Performance through Job Satisfaction..